Analyzing the Operational Performance of Ro-Ro Terminals Using Vessel and Vehicle Queue Time Indicators: A Case Study at Tanjung Perak Port, Surabaya - Erwan Khanissuma; Ulfi Pristiana; Esti Hari Prastiwi (International Forum of Researchers and Lecturers, 2025)
The rapid increase in Ro-Ro (Roll-On/Roll-Off) vessel and vehicle traffic at Tanjung Perak Port, Surabaya, has exposed critical inefficiencies in port operations, particularly at key berths such as Jamrud Utara and Jamrud Selatan. These inefficiencies manifest as prolonged queuing times for Ro-Ro vessels and land-based vehicle congestion, leading to delays in cargo handling and increased operational costs. This study aims to evaluate the operational performance of Ro-Ro terminals based on queue time indicators for both Ro-Ro vessels and vehicles. Employing a quantitative descriptive approach, the research integrates the M/M/c queuing model and Fishbone Diagram analysis to identify systemic causes of operational delays and overcapacity. The study reveals that berth utilization rates exceed 75%, indicating saturation, while limited buffer zones and disorganized traffic flow exacerbate vehicle queues. As a case study, the findings offer data-driven insights and practical recommendations, including schedule optimization, dedicated traffic lanes, and infrastructural upgrades to mitigate congestion. The proposed framework not only enhances service efficiency at the port but also contributes to broader logistics performance in Eastern Indonesia. By combining classical queuing theory with root cause analysis, this research introduces a methodological synergy that can be replicated across other Ro-Ro terminals facing similar challenges. The findings underscore the urgent need for integrated port traffic management and infrastructural adaptability in response to growing maritime logistics demands.